2010
DOI: 10.1016/j.anaerobe.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Sudan azo dyes and Para Red degradation by prevalent bacteria of the human gastrointestinal tract

Abstract: Sudan azo dyes have genotoxic effects and ingestion of food products contaminated with Sudan I, II, III, IV, and Para Red could lead to exposure in the human gastrointestinal tract. In this study, we examined thirty-five prevalent species of human intestinal bacteria to evaluate their capacity to degrade Sudan dyes and Para Red. Among these tested bacterial strains, 23, 13, 33, 30, and 29 out of 35 species tested were able to reduce Sudan I, II, III, IV, and Para Red, respectively, to some extent. Bifidobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 41 publications
2
64
0
Order By: Relevance
“…246,247 Xu et al demonstrated a variable degree of efficiency in the reduction of Sudan azo dyes and Para Red by 35 prevalent human intestinal microbes in vitro. 248 In contrast, Sudan azo dyes and their metabolites selectively inhibit the growth of some human intestinal microorganisms, 249 which may suggest a potential impact on gut microbiome after long-term exposure. In summary, although there are tantalizing glimpses into the effect of azo dyes on microbes in vitro, more data from animal and human studies are keenly awaited.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…246,247 Xu et al demonstrated a variable degree of efficiency in the reduction of Sudan azo dyes and Para Red by 35 prevalent human intestinal microbes in vitro. 248 In contrast, Sudan azo dyes and their metabolites selectively inhibit the growth of some human intestinal microorganisms, 249 which may suggest a potential impact on gut microbiome after long-term exposure. In summary, although there are tantalizing glimpses into the effect of azo dyes on microbes in vitro, more data from animal and human studies are keenly awaited.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Almost 100 % of azoreductase activity of E. coli was found in the cytoplasm and proved to be unable to significantly reduce water-insoluble azo dyes, whereas 55 % of the azoreductase activity of Enterococcus faecalis was membrane bound and capable of reducing the azo bond of some water-insoluble dyes (Xu et al, 2010).…”
Section: Azoreduction By the Intestinal Microfloramentioning
confidence: 99%
“…These data suggest that Sudan I caused breaks in DNA strands and chromosomes. Sudan II causes mutations in Salmonella Typhimurium TA 1538 in the presence of a rat liver preparation (Garner & Nutman, 1977;Xu et al, 2010). Concern about the safety of Sudan III, which is used in cosmetics, has arisen from its potential metabolic cleavage by skin bacteria producing 4-aminoazobenzene and aniline (Pielesz et al, 2002), and Sudan IV has been shown to require reduction and microsomal activation in order to be mutagenic (Brown et al, 1978).…”
Section: Reductive Metabolismmentioning
confidence: 99%
“…The direct mutagenicities of Alizarin Yellow GG and Acid Alizarin Yellow R were eliminated by reduction, but in the presence of the exogenous metabolic system (S9), the resulting products were mutagenic and exhibited frame-shift activity (Brown et al, 1978;Combes & Haveland-Smith, 1982). The Sudan dyes I, II, III and IV are oil-soluble azo dyes (1-amino-2-naphthol-based azo dyes), widely used in coloring plastics, leather, fabrics, printing inks, waxes and floor polishes Xu et al, 2010). Sudan I is a liver and urinary bladder carcinogen in mammals and is also considered as a possible human mutagen, since it can produce the benzenediazonium ion during metabolism catalyzed by cytochrome P450, which could be the mechanism by which Sudan I is activated leading to a carcinogenic final product (Stiborová et al, 2002(Stiborová et al, , 2005Xu et al, 2010).…”
Section: Reductive Metabolismmentioning
confidence: 99%
See 1 more Smart Citation